Pengembangan Media PASAKA (Papan Kosakata) Pada Pembelajaran Bahasa Indonesia Untuk Meningkatkan Keterampilan Membaca Permulaan Siswa Kelas 2 Sekolah Dasar - Kartika , Dea; Robiatul Munajah (Journal of Practice Learning and Educational Development, 2026)
The lack of interest in reading and innovation in learning media at SDN Pancoran 03 has resulted in low student interest and understanding of Indonesian language subjects. This study aims to develop PASAKA (Vocabulary Board) learning media to develop early reading skills, to determine the results of its development, and to measure the effectiveness of its use in Indonesian language learning. The method used is Research and Development with the ADDIE model which includes analysis, design, development, implementation, and evaluation. The research subjects were 24 2nd grade students of SDN Pancoran 03. The validation results from media experts obtained 94%, linguists 90%, and material experts 98% with each category "very feasible". The trial results showed an increase in student learning outcomes with a pre-test percentage of 65.41% while the post-test was 90.4%, with an N-Gain value of 0.71 which is included in the high improvement category. Based on the research results, it can be concluded that the development process for the PASAKA (Vocabulary Board) learning media was systematic and tailored to students' needs. Experts have declared this learning media highly suitable for use in the learning process. Furthermore, this learning media has proven effective in helping students understand Indonesian language learning in Chapter 1, the topic "Recognizing Feelings."